Representing conflict: an analysis of The Chronicle's coverage of the Gukurahundi conflict in Zimbabwe between 1983 and 1986 - Santos, Phillip (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
This research is premised on the understanding that media texts are discourses and that all discourses are functional, that is, they refer to things, issues and events, in meaningful and goal oriented ways. Nine articles are analysed to explicate the sorts of discourses that were promoted by The Chronicle during the Gukurahundi conflict in Zimbabwe between 1982 and 1986. It is argued that discourses in the news media are shaped by the role(s), the type(s) of journalism assumed by such media, and by the political environment in which the news media operate. The interplay between the roles, types of journalism practised, and the effect the political environment has on news discourses is assessed within the context of conflictual situations. This is done using insights from the theoretical position of peace journalism and its critique of professional or mainstream journalism as promoting war/violence journalism. Using the case of The Chronicle's reportage of the Gukurahundi conflict in Zimbabwe, it is concluded that, in performing the collaborative role, state owned/controlled media assume characteristics of war/violence journalism. On the other hand, it is concluded that The Chronicle developed practices consistent with peace journalism when it both espoused the facilitative role and journalistic objectivity. These findings undermine the conventional view among proponents of peace journalism that in times of conflict, the news media should be interventionist in favour of peace and that they should abandon the journalistic norm of objectivity which they argue, promotes war/violence journalism.
Keywords: The Chronicle (Zimbabwe); Zimbabwe -- History -- 1980-; Zimbabwe -- Politics and government -- 1980-; Mass media -- Political aspects -- Zimbabwe; Mass media -- Moral and ethical aspects -- Zimbabwe; Journalistic ethics -- Zimbabwe; Journalism -- Objectivity -- Zimbabwe; War in mass media -- Zimbabwe; Violence in mass media -- Zimbabwe; Mass media and peace -- Zimbabwe; Discourse analysis